Analysis and Optimization of Organic Tandem Solar Cells by Full Opto-Electronic Simulation - Aeberhard, Urs; Schiller, Andreas; Masson, Yannick; Zeder, Simon J.; Blülle, Balthasar; Ruhstaller, Beat (Frontiers in Photonics, 2022)
This paper reports on the analysis and optimization of high-efficiency organic tandem solar cells via full opto-electronic device simulation on continuum level and using a hopping model for the explicit description of the charge recombination junction. Inclusion of the electrical sub-cell interconnection allows for a rigorous assessment of the impact of the internal charge distribution and associated built in fields as well as quasi-Fermi level profiles on the measured device characteristics. It enables the direct evaluation of the external quantum efficiency in a simulation that follows closely the measurement protocol, and sheds light on complications related to the dependence of the band profile on the illumination conditions. The study also points at fingerprints of insufficient junction quality in the electrical characteristics of the tandem device. After studying the impact of key electrical parameters such as, carrier mobility, lifetime and interface hopping rate, onto the device characteristics, the latter are optimized not only optically, but also electronically, adding in both cases an increasing number of layers to the parameters of the global optimization procedure. An improvement of 2% absolute power conversion efficiency by using the full opto-electronic optimization as compared to optical optimization only is found.